Mohamad Djazman and Muhammadiyah Cadre Education: Case Study of Pondok Hajjah Nuriyah Shabran Universitas Muhammadiyah Surakarta - Muslam, Muhammad; Santoso, M. Abdul Fattah (Muhammadiyah University Press, 2018)
The institutionalization of Mohamad Djazmanâs idea to provide intensive education for Muhammadiyah cadres has been realized in the establishment of Pondok Hajjah Nuriyah Shabran or commonly known as Pondok Shabran. The idea is discussed in the present qualitative research with descriptive analysis method. The establishment of Pondok Shabran has contributed to the creation of cadres who have resolute ideology, high militancy, moral characters, the capacity to perform Islamic propagation and the contribution in community life, simultaneously and integratively. Nevertheless, the current phenomenon indicates the re-emergence of caderization problems as the consequence of the sub-optimal implementation of Mohammad Djazmanâs notion. Therefore, the corroboration of the initial idea is required since it is very appropriate and can be a solution for the current and future problems.